Repetition Analysis within the poem"Merindukanmu" in the Poetry Anthology of Parrots - Kasma Amin; Putri Nurfadila (Tamaddun Life, 2017)
Creating a poem must understand a language style that is attractive to the reader. This study aims to describe the types of repetitive language styles used in poetry. The method used is a content analysis method with a structural approach. The data in this study are in the form of words, phrases, and sentences contained in the poem 'Merindukanmu'. The research result shows a picture of refraction in the creation of the poem 'Merindukanmu'.